Hypercoagulability and Risk of Venous Thromboembolic Events in Endogenous Cushing's Syndrome: A Systematic Meta-Analysis - Wagner, Jeffrey; Langlois, Fabienne; Lim, Dawn Shao Ting; McCartney, Shirley; Fleseriu, Maria (Frontiers in Endocrinology, 2019)
Background: Hypercortisolism has been implicated in the development of venous thromboembolic events (VTE). We aimed to characterize VTE risk in endogenous Cushing's syndrome (CS) patients, compare that risk to other pathologies, and determine if there are any associated coagulation factor changes. Methods: Medline and Scopus search for “hypercortisolism” and “thromboembolic disease” from January 1980 to April 2017 to include studies that reported VTE rates and/or coagulation profile of CS patients. A systematic review and meta-analysis were performed. Results: Forty-eight studies met inclusion criteria. There were 7,142 CS patients, average age was 42 years and 77.7% female. Odds ratio of spontaneous VTE in CS is 17.82 (95%CI 15.24–20.85, p < 0.00001) when comparing to a healthy population. For CS patients undergoing surgery, the odds ratio (both with / without anticoagulation) of spontaneous VTE is 0.26 (95%CI 0.07–0.11, p < 0.00001)/0.34 (0.19–0.36, p < 0.00001) when compared to patients undergoing hip fracture surgery who were not treated with anticoagulants. Coagulation profiles in patients with CS showed statistically significant differences compared to controls, as reflected by increases in von Willebrand factor (180.11 vs. 112.53 IU/dL, p < 0.01), as well as decreases in activated partial thromboplastin time (aPTT; 26.91 vs. 30.65, p < 0.001) and increases in factor VIII (169 vs. 137 IU/dL, p < 0.05). Conclusion: CS is associated with significantly increased VTE odds vs. general population, but lower than in patients undergoing major orthopedic surgery. Although exact timing, type, and dose of anticoagulation medication remains to be established, clinicians might consider monitoring vWF, PTT, and factor VIII when evaluating CS patients and balance advantages of thromboprophylaxis with risk of bleeding.